Effect of different particle size reduction techniques on the nefopam and aciclovir dispersity - Pinchukova, N.A.; Lyapunov, N.A.; Bezuglaya, E.P.; Voloshko, A.Yu.; Lyapunov, A.N.; Merko, M.A.; Chebanov, V.A. (Functional Materials, 2015)
Presents the results of application of different particle size reduction approaches to the drug substances - aciclovir and nefopam, namely, wet milling, ultrasonic (US) dispergation, US crystallization and US antisolvent precipitation. All ultrasonic experiments were performed at two operation frequencies - 22 and 44 kHz. It was shown that the crucial parameters in US processes were US output power and sonication time, while the US frequency had a minor effect within the studied power range. US antisolvent precipitation showed the best results among the applied techniques yielding micron-sized particles of aciclovir, which makes this method a very promising technique in nanocrystallization area. The obtained study results provide an opportunity to choose the optimal particle reduction technique depending on the necessary particle size of drug substance suitable for a particular dosage form.